Sintering mechanisms of partially stabilized zirconia (TZ3Y) with ZnO and Co3O4 as sintering additives - Marcomini,R. F. (2021)
Abstract In this work, the sintering mechanisms of 3 mol% yttria-stabilized zirconia (TZ3Y) and TZ3Y containing 0.3 wt% of ZnO or Co3O4 were analyzed by determining the apparent activation energy of sintering from dilatometry data and observing the evolution of microstructure. Dilatometry test was performed at a heating rate ranging from 5 to 20 °C/min from room temperature up to 1500 °C. The main mechanism of each sintering additive for the studied samples was revealed from the variation of the sintering activation energy as a function of the relative density and scanning electron microscopy images. The mechanism for the ZnO additive was the formation of a liquid phase at the beginning of the sintering process, while the Co3O4 additive acted via solid-state sintering by increasing cation diffusivity.